Design and stability of fuzzy logic multi-regional output controllers - Domański, Paweł; Brdyś, Mieczysław A.; Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Design and stability analysis of fuzzy multi-regional digital controllers is considered in the paper. The controllers are based on a notion of N ARMAX systems, very similar to the Takagi-Sugeno fuzzy model. The nonlinear system is approximated by a number of linear subsystems. Linear controllers are designed for all subsystems.
Keywords: nonlinear output control; fuzzy logic; Takagi-Sugeno models; stability conditions